Use of Pyrene for Quantitative Fluorescence Observation of Li-Grease around EHL Contacts - David Kostal; Shugo Onitsuka; Hiroyoshi Tanaka; Joichi Sugimura; Ivan Krupka; Martin Hartl (Tribology Online, 2020)
This paper presents a simple approach for the use of pyrene as fluorescence dye for the observation of the EHL contacts and behavior of lubricants without natural fluorescence properties. Dependence of the light emission of pyrene on its concentration was studied and also, specific emission and excitation spectrum for pyrene dissolved in PAO was found. A mercury lamp was used as the source of the excitation light with proper filter set according to the fluorescence spectrum. Pyrene’s excimer proved to be very resistive against photobleaching and stable in time. This paper also describes experimental methodology on how to improve fluorescence properties of greases by adding pyrene and this approach was also verified by experiments to ensure that there was no influence on grease or pyrene’s emission. This paper also discusses the calibration procedure for valid quantitative experiments.